2009
DOI: 10.1016/j.exphem.2009.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Factor VIII−pulsed dendritic cells reduce anti−factor VIII antibody formation in the hemophilia A mouse model

Abstract: Objective Hemophilia inhibitor formation is a T-cell dependent immune response to infused factor VIII (F.VIII). As immature dendritic cells (DCre) regulate immune response and promote tolerance, we evaluated F.VIII-pulsed DCre, propagated from bone marrow in the presence of GM-CSF and TGFβ, in achieving F.VIII tolerance. Methods The effects of intravenous F.VIII-pulsed DCre in C57BL/6 hemophilia A mice were determined by total F.VIII inhibitory antibodies, T cell proliferation, thymidine uptake, cytokine pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 31 publications
6
20
0
Order By: Relevance
“…Qadura and colleagues reported that infusion of antigen-pulsed immature DCs modestly but not significantly reduced anti-FVIII antibody titers in hemophilia A mice (Qadura et al, 2008). Consistent with this report, Ragni and colleagues reported that adoptive transfer of TGF-b 1 -treated and antigen-pulsed DCs in hemophilia A mice decreased anti-FVIII antibody titers in the mice, for up to 3 weeks (Ragni et al, 2009), but did not report antigen-specific tolerance. Su and colleagues reported a decrease in anti-FVIII antibody titers when using DCs modified with foamy viral vector expressing human FVIII (Su et al, 2011).…”
Section: Introductionsupporting
confidence: 59%
“…Qadura and colleagues reported that infusion of antigen-pulsed immature DCs modestly but not significantly reduced anti-FVIII antibody titers in hemophilia A mice (Qadura et al, 2008). Consistent with this report, Ragni and colleagues reported that adoptive transfer of TGF-b 1 -treated and antigen-pulsed DCs in hemophilia A mice decreased anti-FVIII antibody titers in the mice, for up to 3 weeks (Ragni et al, 2009), but did not report antigen-specific tolerance. Su and colleagues reported a decrease in anti-FVIII antibody titers when using DCs modified with foamy viral vector expressing human FVIII (Su et al, 2011).…”
Section: Introductionsupporting
confidence: 59%
“…29,30 In those studies, naive animals infused with FVIII-pulsed tDCs showed modest reductions in inhibitor titers, in response to subsequent immunization. 29,30 We obtained similar results in this study (Figure 2). The degree of immune suppression is likely dependent on the amount of antigen tDCs present to Teffs and Tregs, and the length of time over which antigen presentation occurs.…”
Section: Discussionmentioning
confidence: 98%
“…The studies that have demonstrated complete suppression of T cell responses to foreign antigens by ex vivo pulsed tDCs used concentrations of antigen in culture media that were 2-3 logs higher than the concentration of FVIII fed to tDCs in the studies performed in hemophilic mice. 22,24,29,30 The additional cost of pulsing tDCs at such high protein concentrations could be a significant barrier to employing this strategy. Furthermore, FVIII is a much larger protein, and contains many more immunogenic domains, than the antigenic peptide fragments employed in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…29 Suppression of the immune response to FVIII in naive hemophilia A mice was also induced by delivery of immature DCs loaded with FVIII antigen. 30,31 In addition, durable suppression of the T cell and inhibitor responses to hFVIII in naive and preimmunized hemophilic mice was shown after infusion of retroviral vector modified B cells expressing fusion proteins of the A2 or C2 domains of FVIII linked to the IgG heavy chain. 28 However, it is difficult to directly compare the efficacy of different published methods for suppressing the immune response to FVIII in hemophilia A mice.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31] Treatment of naive hemophilia A mice with high doses of oral and nasal FVIII antigen suppressed inhibitor formation to subsequent hFVIII immunization and the effect could be adoptively transferred with CD4 + splenocytes. 29 Suppression of the immune response to FVIII in naive hemophilia A mice was also induced by delivery of immature DCs loaded with FVIII antigen.…”
Section: Discussionmentioning
confidence: 99%